1998
DOI: 10.1007/bf02375879
|View full text |Cite
|
Sign up to set email alerts
|

Copper diffusion in copper sulfide: a systematic study

Abstract: Abstract.Copper sulfide Cu2_xS is a model mineral for chalcogenides because of the existence of a non-stoichiometric compounds series in the range Cu2S -CuS in which properties change with x. For this reason, we have studied the influence of the mineral composition on the diffusion in this solid.Electrochemical Impedance Spectroscopy (EIS) applied to CU2_xS/cupric sulfate electrolyte was the main investigation technique. It enabled us to work at the equilibrium potential at which the composition is fixed and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Copper sulde is well known to form a wide variety of nonstoichiometric and mixed phases, djurleite, digenite, etc. 51,52 Utilizing its intrinsic cationic deciencies, [53][54][55][56][57] a heterostructured Cu 2 S-In 2 S 3 nanocrystal has been reported by using djurleite Cu 1.94 S nanocrystals as a catalyst. 31 Also, Cui et al 58 reported that heterostructured CuInS 2 nanorods were epitaxially overgrown on chalcocite Cu 2 S nanodisks, starting with nucleation of Cu 2 S nanodisks.…”
Section: Resultsmentioning
confidence: 99%
“…Copper sulde is well known to form a wide variety of nonstoichiometric and mixed phases, djurleite, digenite, etc. 51,52 Utilizing its intrinsic cationic deciencies, [53][54][55][56][57] a heterostructured Cu 2 S-In 2 S 3 nanocrystal has been reported by using djurleite Cu 1.94 S nanocrystals as a catalyst. 31 Also, Cui et al 58 reported that heterostructured CuInS 2 nanorods were epitaxially overgrown on chalcocite Cu 2 S nanodisks, starting with nucleation of Cu 2 S nanodisks.…”
Section: Resultsmentioning
confidence: 99%
“…[48][49][50] In the anodization process, an electric field, the magnitude of which is proportional to the anodization voltage, is induced between copper anode and the cathode that enhances the diffusion rate of Cu + in the copper sulfide film. The diffusion coefficient [51][52][53] of Cu in copper sulfides is 10 4 -10 5 cm 2 s −1 . Fast Cu + diffusion coupled with high affinity between copper and sulfur is the cause of fast kinetics of the vertically aligned copper sulfide nanostructure growth.…”
Section: Growth Mechanism Of Anodized Copper Sulfide Nanostructuresmentioning
confidence: 99%
“…Research on the historical Cu 2 S/CdS solar cell has been abandoned due to long term stability problems from degradation of the Cu 2 S layer in air, 18 but also from inevitable diffusion of copper ions into the CdS layer 11,12,19 due to the unusually high mobility of the Cu atoms. 20 Nevertheless, alternative solar cell concepts like the Cu 2 S/ZnO-heterostructure, for which an attainable power conversion of g ¼ 17:8% has been predicted, 21 the ZnO/Cu 2 S/Cu 2 O p-i-n structure 22 and the Cu 2 S/Ti 2 O heterojunctions [23][24][25] are feasible.…”
Section: Introductionmentioning
confidence: 99%